Optimal design of fluid viscous dampers for buildings - Chaw, Suu Hlaing. (2011)
One of the natural disasters called earthquake has always threatened the human live and their properties. Due to the damage of the structure and its content, many lives and economy of the nation have been suffered. Therefore, the main objective of this report is to reduce inter-storey drifts and floor acceleration to limit or avoid damage not only to the structure but also to its content. One of the widely implemented ways to protect the building from earthquake motion is to install fluid viscous damper to certain floors.Firstly, the author will introduce basic knowledge for earthquake or ground excitation. In